Isolation and characterization of Borrelia burgdorferi from blood of a bird captured in the Saint Croix River Valley. - McLean, R G (1993)
Field investigations were conducted to further evaluate the role of birds in the maintenance and dissemination of Borrelia burgdorferi. Blood specimens were taken from 39 passerine birds of 17 species captured during June 1991 at the Saint Croix National Riverway in Wisconsin, and one isolate, WI91-23, was cultured from an adult song sparrow (Melospiza melodia). This isolate was shown to be infectious for Peromyscus leucopus and Mesocricetus auratus (golden hamster). Isolate WI91-23 was confirmed as B. burgdorferi by immunofluorescence assay by using species-specific anti-OspA monoclonal antibodies H3TS and H5332 and anti-OspB antibody H5TS. Isolate WI91-23 was compared with Borrelia anserina Es, Borrelia hermsii MAN-1, and other B. burgdorferi strains (ATCC 53210, CT-1, and Catharus fuscescens [veery] liver 10293). Pulsed-field gel electrophoresis of in situ-lysed spirochetes revealed that the DNA plasmid profile of WI91-23 was most similar to those of plasmids from B. burgdorferi and most different from those of plasmids from B. anserina and B. hermsii. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis indicated that the protein profile of WI91-23 was like that of other B. burgdorferi strains studied, with dominant proteins corresponding to OspA and OspB, and that it differed from the protein profiles of B. anserina and B. hermsii. These findings indicate that passerine birds may serve as reservoirs for B. burgdorferi.